Therapeutic Potential of Long Non-Coding RNAs of HIV-1, SARS-CoV-2, and Endogenous Retroviruses - Ruiz Ramírez, Andrea Virginia; Prado Montes de Oca, Ernesto (Frontiers in Virology, 2022)
Long non-protein coding RNAs (lncRNAs, predicted to be up to 200,000 in the human genome) are nucleic acids of more than 200 nucleotides that play primordial roles in the regulation of chromatin states, but also are capable of decoying or scaffolding proteins (e.g. transcription factors, TFs; host and viral proteins), DNA (e.g. promoters and enhancers) and RNA (e.g. miRNAs, hnRNAs) in 3D conformations acting in a chaperonin-like fashion. Specifically, lncRNAs modulate gene expression during the regulatory layers of transcription, RNA processing (splicing and indirectly editing), translation and post-translational modifications including phosphorylation, acetylation and ubiquitination. Accumulated evidence indicates that lncRNAs regulate antiviral immune responses mainly by transcription of IFN regulatory factors 1 (IRF1) and 4 (IRF4) which contribute to type I interferon (IFNα and IFNβ) upregulation. Some of the most common TFs regulated by lncRNAs are TP53, CTCF, MYC, SOX2, EZH2 SFPQ, SUZ12, STAT1, STAT3 and NF-kappa B. In this review, the known functions of selected lncRNAs genes in HIV/AIDS (MALAT1, HEAL, NRON, TAR-gag, TP53COR1/lincRNA-p21, NEAT1, NKILA, LINC01426-formerly Uc002yug.2,- FAS-AS1, LINC00173-formerly FLJ42957/NCRNA00173,- GAS5 and HIV-encoded antisense lncRNA) and COVID-19 (EGOT, MALAT1, NEAT1, DANCR, HOTAIR, FENDRR, LINC1505, FALCOR and HISLA) are discussed. Furthermore, MALAT1 is also involved in subsequent complications as deep vein thrombosis (DVT) in COVID-19. In addition, after the increased understanding of the role of lncRNAs from Human Endogenous Retroviruses (HERVs, predicted to be at least 582 different with 725,763 repeats of them in the human genome) in cancer (TROJAN) and heart development (BANCR), transcripts of HERVs as lnc-EPAV and lnc-ALVA1-AS1 have recently draw attention as host protective agents against viral infections. A deeper knowledge of host and viral lncRNAs interactions and their regulation, will pave the way for the design of novel drugs inspired in host- and viral-encoded lncRNAs. These novel drugs have the potential to reduce the burden of HIV/AIDS and COVID-19 twofold: 1) by increasing their efficacy and 2) by minimizing the side effects of current drugs. We expect that lncRNA drugs will be able to modulate human and viral transcription in an unprecedented way but still effectively maintain homeostasis by deploying functionality below the pathogenic threshold.